A score for estimating survival in idiopathic pulmonary fibrosis with rest SpO2>88% - Soares, Maria Raquel; Pereira, Carlos; Ferreira, Rimarcs; Nei Aparecida Martins Coletta, Ester; Silva Lima, Mariana; Muller Storrer, Karin (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Background: Prediction models for survival at baseline evaluation have been proposed in IPF but some are difficult to use. The aim of present study was to develop a new mortality risk scoring system for patients with IPF at initial evaluation. Methods: One hundred twenty with definitive IPF were selected through a review of standardized medical records for interstitial lung diseases. Patients with resting SpO2<89% were excluded. Significant individual predictors we derived by a Cox proportional hazards model and transformed in categorical data according to cut-off points. Beta coefficients for each predictor were similar, so a score was created considering the sum of dichotomic (0 or 1) transformed variables. Findings: Median follow-up time was 37.5 months. At the end of follow-up, 80 patients had died. Independent predictors of mortality by multivariate analysis included dyspnea (at rest or to light or moderate activities), FVC<70%,FEV1/FVC>0.89 and DLCO ≤ 40%. Resting SpO2 and ExSpO2 were excluded in final analysis. The hazard ratios ranged from 1.95 for dyspnoea to 2.30 for DLCO. When the total score was 0 (Stage I, n=28), median survival time was 68 months; when 1 or 2 (Stage II, n=69), it was 45 months; and when 3 or 4 (Stage III, n=23), it was 19 months (log rank= 60.44, p<0.001). Interpretation: The score can separate IPF patients with high, intermediate and low survival. (Sarcoidosis Vasc Diffuse Lung Dis 2015; 32: 121-128)